Farmers’ use of, and attitudes towards, Rhizobium and recommended rate of fertilizers in mungbean cultivation in southern Bangladesh - Hossain, Md. Khaled; Atikuzzamman, M.; Laing, Alison M.; Krupnik, Timothy J. (AMD, 2024)
Mungbean, the third most important pulse in Bangladesh, is widely grown in Patuakhali, which ranks third nationally in cultivation area (5,089 ha). However, yields are low due to environmental challenges like cyclones, salinity, and water scarcity, as well as limited adoption of effective agronomic practices. Techniques such as line-sowing, timely weed control, proper fertilizer use, and biofertilizers like Rhizobium can boost productivity, but adoption remains limited. Farmers' decisions are influenced by risk perceptions, resource constraints, and opportunity costs. A 2021 survey in Patuakhali explored these barriers to inform strategies for sustainable mungbean farming.